GRAPHIC DESIGN IN FILM: BUILDING CHARACTER IDENTITY AND VISUAL STYLE IN THE GREAT GATSBY (2013) - Tude, Helena; Varzim, Marta (Design/Arts/Culture, 2020)
Graphic design and cinema have worked together since the early days of filmmaking, driven by the effort to develop autonomous visual narratives in silent films, in much through the use of intertitles. It is meaningful to recognize how graphic design elements have invariably been a part of cinema’s hybrid language, as a material of expression manifested through the visual channel together with the filmed image. The different technological milestones that shaped cinema’s development also directly influenced the use of graphic language in movies, which became more complex with time. These graphic elements are present throughout an entire film narrative, from the choice of verbal, pictorial and schematic elements in titles and animations, to the creation (and curation) of printed or handmade graphic props, signage and logos filmed by the camera. Together, they form a movie’s graphic identity, which helps to convey meaning to the narrative as well as to bring a more dynamic and authentic storytelling. Through a case study of Hollywood’s 2013 movie adaptation of the literary masterpiece The Great Gatsby, this paper intends on exemplifying the strategic use of graphic design elements throughout the movie – in the physical and virtual formal natures – aiding in the construction of characters’ identities, contextualized into the roaring 1920’s aesthetics, as well as defining a clear visual style that is consistent with director Baz Luhrmann’s unique vision for the movie. In this way, the objective is to bring awareness to the potential of graphic design in building cinematic worlds that are historically accurate, aesthetically rich, and emotionally identifiable.